A dinâmica variável tu/você em cartas piauienses novecentistas: um percurso histórico - Luiz Egito de Souza Barros (2024)
In this Doctoral Thesis, the main proposal is the study, in light of the principles of historical sociolinguistics (HERNÁNDEZ-CAMPOY & SCHILLING, 2012), of the variation between forms of reference to the 2nd person singular subject (tu (you)/você (you)) based in the written production of illustrious people from Piauí in the 20th century, more specifically between the 1920s and 1990s (1920s and 1990s). Considering that the focus is on presenting an analytical description of the tu/você (you) alternation, in the light of the Theory of Power and Solidarity (BROWN & GILMAN, 1960), in letters produced, during the 20th century (1920-1990), by Piauí, considering the social relations that underpin them, we understand that the innovativeness of the theme is also evident due to the fact that it has not been addressed in relation to Piauí editors in past synchronies. Let us also add the fact that we detected evidence, based on the Linguistic Atlas of Brazil (ALiB), which reveals the low productivity of tu (in only 13% of the data), cf. discussed by Lopes et alii (2018, p. 118), guiding the starting point of this analysis, which is to turn to the “present to explain the past” (TRUDGILL & HERNÁNDEZ CAMPOY 2007, p. 299). The main hypothesis is that você (you) would already be seen as more productive than tu (you) in the 19th century era of PB, as already observed by Scherre et alii (2021) in the light of Deus (2009) and Cardoso (2008) for the data from AliB. In general, we found the prevalence of você (you) (60.03%), although in intense alternation between tu (you) (39.97%) in letters from Piauí. With regard to the contexts of social relations that subsidize the forms tu and você (you), we see the productivity of você (you) not only in symmetrical relationships, but also in descending asymmetrical ones, highlighting the semantics of Solidarity in the reality of nineteenth-century Brazilian Portuguese. Still in relation to você (you), we found that your productivity is favored in the contexts of the third person verbal, você-subject and the written production of elderly and adult writers, following the results of Souza (2021) and Souza (2012) also conducted by analyzing historical samples. Therefore, we believe that this Thesis will fill a gap in relation to sociolinguistic studies on the tu/você (you) dynamics in Piauí lands of past synchronies.